2020
DOI: 10.3390/nano10112225
|View full text |Cite
|
Sign up to set email alerts
|

In Situ and Real-Time Nanoscale Monitoring of Ultra-Thin Metal Film Growth Using Optical and Electrical Diagnostic Tools

Abstract: Continued downscaling of functional layers for key enabling devices has prompted the development of characterization tools to probe and dynamically control thin film formation stages and ensure the desired film morphology and functionalities in terms of, e.g., layer surface smoothness or electrical properties. In this work, we review the combined use of in situ and real-time optical (wafer curvature, spectroscopic ellipsometry) and electrical probes for gaining insights into the early growth stages of magnetro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 150 publications
0
13
0
Order By: Relevance
“…For all curves, the resistivity ρ exhibits an initial sharp drop after which it reaches a steady-state value ρ ss . We have previously shown that 53,54,57,61 : (i) the nominal thickness at which ρ ss is established (denoted as Θcont) signifies the formation of continuous layer; and (ii) the magnitude Θcont can be used as a proxy for assessing the character of growth, i.e., decrease of Θcont indicates that the film grows flatter and 2D morphology is promoted. The data show that all alloying elements used yield Θcont values that are smaller than that of pure Ag (Θcont = 81 ML; black squares), with the maximum decrease achieved for the case of Cu (Θcont = 47 ML; red circles).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For all curves, the resistivity ρ exhibits an initial sharp drop after which it reaches a steady-state value ρ ss . We have previously shown that 53,54,57,61 : (i) the nominal thickness at which ρ ss is established (denoted as Θcont) signifies the formation of continuous layer; and (ii) the magnitude Θcont can be used as a proxy for assessing the character of growth, i.e., decrease of Θcont indicates that the film grows flatter and 2D morphology is promoted. The data show that all alloying elements used yield Θcont values that are smaller than that of pure Ag (Θcont = 81 ML; black squares), with the maximum decrease achieved for the case of Cu (Θcont = 47 ML; red circles).…”
Section: Resultsmentioning
confidence: 99%
“…This is achieved using spectroscopic ellipsometry, a nondestructive optical technique that determines the optical properties of materials by measuring changes in the polarization state of a light beam upon its interaction with the sample under investigation. 67 The methodology used for collecting and analyzing ellipsometric data has been explained in detail in our previous studies, [61][62][63][64] hence here we only summarize key aspects.…”
Section: B In Situ Film Growth Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultra-thin metal films are wildly applicated in metamaterials, plasmonic devices, nanophotonic, and light-emitting diodes [ 1 , 2 ]. Recently, continuous metallic films became a good candidate for the replacement of indium tin oxide (ITO) for flexible optoelectronic devices [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In ref. [ 13 ] the growth of metallic ultra-thin films by continuous dynamic monitoring is reviewed in depth, by combining in situ and real-time optical and electrical probes to analyze the first stages of growth in the MS deposition of a large number of metals with different crystalline structures. In ref.…”
mentioning
confidence: 99%